Factors Affecting the Effectiveness of Inter-Dialectical Accommodation among the Sellers-Buyers Discourse - Abdul Muhid; Hamzah A Machmoed; Abdul Hakim Yassi; Nasmilah Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
In this research, the researchers convince the readers about factors that affecting the effectiveness of Inter-dialectical accommodation among sellers-buyers. In this research, they prove how the theory of Giles cannot cover the discourse among sellers and buyers in terms of accommodation,   which is done in Central Lombok Nusa Tenggara Barat Province. The researchers describe the phenomenon of the inter-dialectical accommodation in the dialect of Meno-mene versus Meriak-meriku. The object of this research is the activities of sellers-buyers in doing the transaction in the market. The data in this research is taken through observation, recording, interview and note taking of the accommodation among sellers and buyers discourse in some markets in Praya Barat, Praya and Jonggat Sub-district. The researchers use the interpretative qualitative method with some data to reflect the condition of sellers versus buyers discourse in the market. The researchers find the preliminary data shows that the Giles Convergence Theory is un-effective or not applicable in the market where sellers and buyers of Meno-mene versus Meriak-meriku assemble and do a transaction. However, the research result shows the un-effectiveness or there is no effect of converging in bargaining. This research reveals that the convergence theory by Giles cannot be generalized into all part of the discourse, especially in the dialect of Meno-mene versus Meriak-meriku.